Activity of Dalbavancin against Bacillus anthracis In Vitro and in a Mouse Inhalation Anthrax Model - Heine, Henry S. (American Society for Microbiology (ASM), 2010)
Bacillus anthracis, the causative agent of anthrax, can produce fatal disease when it is inhaled or ingested by humans. Dalbavancin, a novel, semisynthetic lipoglycopeptide, has potent activity, greater than that of vancomycin, against Gram-positive bacteria and a half-life in humans that supports once-weekly dosing. Dalbavancin demonstrated potent in vitro activity against B. anthracis (MIC range, ≤0.03 to 0.5 mg/liter; MIC(50) and MIC(90), 0.06 and 0.25 mg/liter, respectively), which led us to test its efficacy in a murine inhalation anthrax model. The peak concentrations of dalbavancin in mouse plasma after the administration of single intraperitoneal doses of 5 and 20 mg/kg of body weight were 15 and 71 mg/kg, respectively. At 20 mg/kg, the dalbavancin activity was detectable for 6 days after administration (terminal half-life, 53 h), indicating that long intervals between doses were feasible. The mice were challenged with 50 to 100 times the median lethal dose of the Ames strain of B. anthracis, an inoculum that kills untreated animals within 4 days. The efficacy of dalbavancin was 80 to 100%, as determined by the rate of survival at 42 days, when treatment was initiated 24 h postchallenge with regimens of 15 to 120 mg/kg every 36 h (q36h) or 30 to 240 mg/kg every 72 h (q72h). A regimen of ciprofloxacin known to protect 100% of animals was tested in parallel. Delayed dalbavancin treatment (beginning 36 or 48 h postchallenge) with 60 mg/kg q36h or 120 mg/kg q72h still provided 70 to 100% survival. The low MICs and long duration of efficacy in vivo suggest that dalbavancin may have potential as an alternative treatment or for the prophylaxis of B. anthracis infections.